Organometallic-type reactivity of stable organoboronates for selective (hetero)arene C−H/C-halogen borylation and beyond - Xueting Liu; Daojing Li; Guoao Li; Mengran Wei; Shihao Yuan; Mo Yang; Linke He; Shengda Chen; Zhenxing Li; Liuzhou Gao; Guoqiang Wang; Shuhua Li (Nature Communications)
Abstract Organometallic reagents are essential tools in both academic and industrial laboratories and the polarity separation within the carbon-metal bonds endows them with exceptional reactivities, but also imposes limitations, including air- and moisture-sensitivity, and flammability. Here, we demonstrate that stable and easily accessible benzylic (or allylic) boronate with alkali-metal alkoxide as the activator can act as reactive organometallic reagents. This strategy enables transition metal-free deprotonative C−H borylation of diverse (hetero)arenes. The polar organometallic nature of this process enables predictable and site-selective borylation by targeting the arenes’s most acidic C−H bond. This approach can be coupled with Suzuki-Miyaura reaction to produce C−H arylation products. We have also applied this strategy to the dehalogenative borylation of aryl bromides and anionic polymerization of styrenes. Given the unique stability and structural diversity of organoboronates, their organometallic-type reactivities show promise as a powerful alternative to synthetic methodologies that rely on sensitive organometallic reagents.